Spectral analysis of whole plant ethanol extract of Blepharisrepens (vahl) roth and its fraction - M.Rajan; N.Senthilkumar; G.Jeyabalan (International Journal of Pharmacy and Analytical Research, 2014)
The whole plant of Blepharisrepens (vahl) Roth, have a great medicinal value. The aim of the present study was to determine the chemical profile of ethanolic extract of Blepharisrepens (vahl) Rothand its fractions (by various spectral analysis) which will be useful for its proper identification when therapeutically used. Spectral analysis was done by different analytical methods such as UV, IR, GC-MS and HPTLC studies in ethanol extract (EE) of Blepharisrepens (vahl) Rothand its fractions. In HPTLC analysis, ethanolic extract and its fractions showed the presence of different types of compound with different RF values ranging from 0.01 to 1.05. The GC-MS analysis showed the presence of terpenoids (mono), fatty acids such as hexadecanoic acid (CAS) palmitic acid, heptadecanoic acid(CAS) palmitic acid, benzene dicarboxylic acid, cyclo heptasiloxane, Octadecene -1-ol, octadecenalin ethanol extract and its fractions ofBlepharisrepens (vahl) Roth.